To study the effect of oral supplementation Vitamin D during pregnancy and status of cord blood - Sravanthi Veldanadi; Kavitha Vislavath; Archana Challa; Praveen Dussa; Vasudeva Murali (Asian Journal of Medical Sciences, 2022)
Background: In many nations, low Vitamin D levels in pregnant women have been associated to adverse outcomes for the mother, her baby, and the birth itself. Aims and Objectives: To study the effect of oral supplementation of mothers with high dose vitamin D (2000IU/day) in comparison with maintenance dose (400IU/day) during pregnancy on vitamin D status of cord blood at the time of delivery. Materials and Methods: Randomized single blind controlled trial conducted in 112 mothers recruited in first trimester, randomized into two groups. One group of mothers received 2000 IU/day, one group 400 IU/day till delivery. Mothers are followed up till delivery age, weight, height, and dressing. Results: Vitamin D levels in mothers in study group were showing 88% insufficiency (<20 ng/ml) and 12% sufficiency (>20 ng/ml). Mean values in both groups that is Group A 6.6±2.8, in Group B 6.2±2.2, both means are comparable with P=0.47, but after supplementation mean maternal Vitamin D level that is 13.4±3.6, with P≤0.0001, this shows that there is a statistically significant. There is a statistically significant correlation is observed between maternal and cord blood Vitamin D levels after supplementation. Statistically significant correlation was observed between maternal and cord blood Vitamin D levels. Conclusions: Vitamin D supplementation throughout pregnancy enhances maternal serum and Vitamin D levels at term, according to this study. There is currently sufficient high-quality evidence pertaining to the therapeutic effects of Vitamin D supplementation during pregnancy.